Isolation and Identification of Native Mikoriza Morphology on The Rhizosphere Gluta rengas L. in Jompie Botanical Garden - Muhammad Ilham; Andi Adam Malik; A. Amri; Muhammad Akhsan Akib (Agrotech Journal, 2019)
Alitta Forest, located in the city of Parepare, South Sulawesi, has an area of 84 ha, a portion of this forest area is functioned as part of a botanical garden. The jompie botanical garden has an area of 13.5 ha, with a collection of plants reaching 90 species originating from 81 plant clans and as many as 77 species that have been identified. In addition to a collection of high-level plants, jompie botanical gardens also have a diversity of microorganisms that have not been identified, especially microorganisms that symbiosis with plant roots known as mycorrhiza, so the purpose of this study is to identify and identify the abundance of mycorrhizal spores in the jompie botanical garden found in rhizosphere Gluta renghas L.. The research began with taking the rhizosphere under the stands of wet trees in the jompie botanical garden, which was then continued to identify and calculate the abundance of spores in the microbiology laboratory of Makassar's research and development environment and forestry. The identification results of mikoiza spores native to the jompie botanical garden show that they are found in two genera, namely; Acalauspora sp consisting of two morphotypes, and the genus Glomus sp consisting of one morphotype, with an average spore abundance of 45.3 per 100 grams rhizosphere